2017
DOI: 10.1002/app.46166
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom polysaccharides‐incorporated cellulose nanofiber films with improved mechanical, moisture barrier, and antioxidant properties

Abstract: Mushroom polysaccharides (MP), including white MP, brown MP, and enoki MP, were incorporated into cellulose nanofiber (CNF). Studies on thermal property, structure, crystallinity, and morphology of CNF-MP films revealed that MP was well interacted with and adsorbed onto CNF. Incorporation of MP significantly (P < 0.05) increased tensile strength and reduced water vapor permeability of CNF film. CNF-MP films possessed higher antioxidant activity than CNF only or CNF-chitosan film, and the antioxidant activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…For example, blending mushroom polysaccharides with cellulose nanofibers to create a film can improve the film's tensile strength and elongation at break, while also decreasing its water vapor and oxygen permeability. As a result, the film exhibits superior moisture resistance and oxygen barrier properties ( 174 ).…”
Section: Application Prospect Of Empsmentioning
confidence: 99%
“…For example, blending mushroom polysaccharides with cellulose nanofibers to create a film can improve the film's tensile strength and elongation at break, while also decreasing its water vapor and oxygen permeability. As a result, the film exhibits superior moisture resistance and oxygen barrier properties ( 174 ).…”
Section: Application Prospect Of Empsmentioning
confidence: 99%
“…The derivative films of some natural fiber materials have excellent gas barriers and mechanical properties. However, as food packaging materials, the antioxidant function is usually needed to ensure the quality and safety of food, including extending the shelf life of foods, especially those with a high-fat content [ 190 ]. Packing natural polysaccharides with antioxidant activity into fiber materials is the critical choice to meet the needs of food packaging.…”
Section: Biomedical and Medicinal Application Of Natural Polysaccharidesmentioning
confidence: 99%
“…Whey protein isolate has high water-vapor permeability, which is due to the presence of hydrophilic groups. This can be diminished by introducing functional groups that decrease the hydrophilic sites or incorporation into chitosan nanofibers, which slows down water molecules’ penetration [ 151 ]. It was observed that by incorporating chitosan nanofibers in whey protein isolate films, tensile strength and Young’s modulus increased, but after integrating cinnamon oil in both forms (emulsified and nanolipid carriers), tensile strength and Young’s modulus decreased [ 152 ].…”
Section: The Rationale Of Encapsulation Of Essential Oils Into Polymeric Nanofibersmentioning
confidence: 99%